Megabarcoding dark taxa – Assessing the utility of mass DNA barcoding for phorid fly species discovery - Jiri Vihavainen; Niina Kiljunen; Pekka Pohjola; Jaclyn McKeown; Eveliina Oinonen; Marko Mutanen; Jaakko Pohjoismäki (PLoS ONE, 2025)
Many hyperdiverse, small-bodied insect families contain numerous undescribed species, generally termed “dark taxa”. Scuttle flies (Diptera: Phoridae), being among the most diverse insect groups globally, are a prime example. DNA barcoding can help delineate dark taxa, particularly when integrated with morphology, and/or additional molecular evidence. We sequenced COI -barcodes from 9,120 Finnish phorid specimens and initially identified them using the BOLD database. Furthermore, species identifications of all 843 specimens, belonging to other genera than Megaselia, were confirmed morphologically. Initially, the BOLD-based identifications matched the morphological identifications only in 68% of the cases, primarily due to numerous misidentifications in BOLD. After adjusting the BOLD reference identifications based on morphological analyses of male features, we established a reliable framework for female identification. This is advantageous for future identification of females, as they are often excluded from traditional identification keys. Only two species were discovered as new to Finland, demonstrating that Finnish fauna is well-known, except Megaselia . Although DNA barcodes show great promise for identifying phorids, incorrectly identified reference sequences remain challenging, not the functionality of barcode gene Cytochrome c oxidase subunit I (COI) itself. The number of Megaselia BINs greatly exceeded the known Finnish species count, with many sequences lacking matches in BOLD. This further highlights Megaselia as a particularly dark group, for which genetic tools are essential for uncovering species identities and assessing diversity.